Prevalence of anxiety in people with aphasia after stroke. Issue 12 (2nd December 2017) - Morris, Reg; Eccles, Alicia; Ryan, Brooke; Kneebone, Ian I.
ABSTRACT: Background : Anxiety is common after stroke and is associated with poorer recovery. People with aphasia after stroke are typically excluded from studies of anxiety prevalence and so the number of those affected is unclear. Aims : To make a preliminary estimate of the prevalence of significant anxiety in people with aphasia after stroke. Methods & Procedures : Carers to community-dwelling people with aphasia after stroke, N = 111, completed the Behavioural Outcomes of Anxiety scale (BOA), a modified Hospital Anxiety and Depression Scale – Anxiety sub-scale (HADS-A), and a modified Generalised Anxiety Disorder-7 item (GAD-7) scale to determine the presence of significant anxiety in the person for whom they cared. Associates of anxiety in people with aphasia after stroke were also investigated. Outcomes & Results : The BOA identified 49 people (44%) as having significant anxiety. Findings for the HADS-A = 46 (41%) were similar; however, for the GAD-7, the rate was substantially lower = 18 (16%). Anxiety after stroke had a modest but significant association with younger age (all measures) and with the Frenchay Aphasia Severity Test scores (BOA and HADS-A only). Conclusions : The prevalence of anxiety in people with aphasia after stroke is high and likely higher than in those with stroke with no aphasia when measured using a validated tool for this population. Risk factors for anxiety appear to be severity of aphasia and younger age. This finding should be tempered by the fact that this is a preliminary study in a relatively small sample consisting of those attending stroke groups and the use of caregiver assessments may overestimate the prevalence of mood disorder.